2014
DOI: 10.4103/2231-0762.142028
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of root canal sealer distribution in obturated root canal: An in-vitro study

Abstract: Background and Objectives:Endodontic sealer is currently regarded with such importance in the root canal treatment that it is often considered to be more important than the core obturating material itself. Sealer with the least film thickness is favorable for minimizing microleakage. The aim of the study is to compare sealer distribution in root canal using three different sealers with three different obturation techniques.Materials and Methods:AH plus, Fuji-1, Tubliseal Extended Working Time (EWT) was placed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Tubliseal EWT showed the highest PSCP value, and the Single cone technique showed the higher PSCP value than the lateral and vertical condensation technique at 3 mm and 6 mm sections. 10 M K Wu et al observed sealer distribution in root canals filled by different root filling techniques. AH26 (0.05 mL) dyed with carbon black powder was placed into the prepared root canals of maxillary central incisors using a lentulospiral.…”
Section: Discussionmentioning
confidence: 99%
“…Tubliseal EWT showed the highest PSCP value, and the Single cone technique showed the higher PSCP value than the lateral and vertical condensation technique at 3 mm and 6 mm sections. 10 M K Wu et al observed sealer distribution in root canals filled by different root filling techniques. AH26 (0.05 mL) dyed with carbon black powder was placed into the prepared root canals of maxillary central incisors using a lentulospiral.…”
Section: Discussionmentioning
confidence: 99%
“…The gutta-percha closely adapted to the dentin wall, so the sealer squeezed out from portion, and thus formed voids between the gutta-percha and dentin interface or to the displacement of the compressed gutta-percha. [20]…”
Section: Discussionmentioning
confidence: 99%
“…7 Several types of endodontic sealers are commercially available, such as calcium hydroxide-based Acroseal and Sealapex, and epoxy resin-based AH Plus. 8 Sealapex and Acroseal are sealers containing calcium hydroxide, and their dissociation into calcium and hydroxyl ions alkalinize the environment, leaving it unfavorable to bacterial proliferation. 1 Moreover, calcium ions can react with carbon dioxide and reduce the breathing source of anaerobic bacteria.…”
Section: E Faecalis Is Also Ablementioning
confidence: 99%